Digital ischemic necrosis with cryoglobulinemia associated with hepatitis B infection - Arslan, Ferhat; Karagöz, Ergenekon; Mert, Ali (Elsevier Science Bv, 2016)
A 77-year-old male patient presented with a one week history of general worsening condition, with mental status and respiratory insufficiency. He was therefore admitted to the Intensive Care Unit. His past medical history was unremarkable except for hypertension. He had cyanosis of the nose, hands and feet with purple to black discoloration (Fig. 1). Initial laboratory study results were notable for leukocytes: 24,000/mm3, neutrophils: 85%, hemoglobin: 8.6 g/dL, thrombocytes: 120,000/mm3, erythrocyte sedimentation rate (ESR): 110 mm/h, C-reactive protein (CRP): 64 mg/L, aspartate aminotransferase: 83 U/L, alanine aminotransferase: 125 U/L, BUN: 110 mg/dL, creatinine: 3.4 mg/dL. In the differential diagnosis, sepsis with multiorgan failure and coronary artery disease with acute heart failure were considered.
WOS: 000389976100045
PubMed ID: 27857479
Keywords: Digital Ischemic Necrosis; Cryoglobulinemia; Hepatitis B